Supervision and project performance: a principal-agent approach - Chauvet, L; Collier, P; Fuster, A (2008)
This paper applies and extends principal-agent theory to analyze the performance of donor projects. As in many situations, there is variation in the degree of divergence between the interests of the donor (the principal) and the recipient government (the agent). Further, the effort expended on supervision of the agent is a control variable. We first present a principal-agent model that shows that conditional on optimal contracting, the marginal effect of more precise supervision on the likelihood of project success is higher the wider the divergence of interests. We then test this prediction using data on project performance. We are able to measure the degree of divergence between donor and recipient interests, as perceived by the donor, through a donor classification system of recipient governments. Consistent with the theory, we find that donor supervision of projects is significantly more effective in improving project performance where interests are widely divergent.